On new detailed ionogram signatures of Equatorial Plasma Bubbles from non-equatorial station during low solar activity - Trang, Nguyen Thu; Tsunoda, Roland T.; Minh, Le Huy (Vietnam Journal of Earth Sciences, 2015)
A first - time direct comparison between climatology of spread F (SF) observed at Phu Thuy and DMSP, C/NOFS satellite measurements during years of low solar activity conditions 2007 - 2010, together with ionosonde observations under the same solar conditions 1953 - 1955 in Baguio, is made to show good relationship of SF at off-equator and equatorial plasma bubbles over the dip equator. The results showed peak of irregularity activities around June solstice, which again confirmed the breakthrough findings by satellites as one typical characteristics of ionospheric structures during low solar activity. We also found that we cannot use typical types of SF for equatorial stations as the ones observed at non-equatorial stations. Instead, we suggested a new method to classify SF types in the relation to ionospheric structures at the off-equator stations of interest. Consequently, we can explain, in the simplest cases, for the first time, complex range type SF observed at off-equatorial stations and name a new type as indicator of EPB occurrence.References Abdu M.A., R.T. de Medeiros, J.A. Bittencourt and I.S. Batista, 1983, Vertical ionization drift velocities and range type spread F in the evening equatorial ionosphere, J. Geophys. Res. 88 (399). Abdu M.A., J. H. A. Sobral, O. R. Nelson and I.S. Batista, 1985: Solar cycle related range type spread-F occurrence characteristics over equatorial and low latitude stations in Brazil, J. Atmos. Solar-Terr. Phys., 47 (8-10), p.901 - 905. Ajith K. K., S.TulasiRam, M.Yamamoto, T.Yokoyama, V. Sai Gowtam, Y. Otsuka, T. Tsugawa, and K. Niranjan, 2015: Explicit characteristics of evolutionary-type plasma bubbles observed from Equatorial Atmosphere Radar during the low to moderate solar activity years 2010-2012, J. Geophys. Res. Space Physics, 120, doi:10.1002/2014JA020878. Basu B., 1997: Generalized Rayleigh-Taylor instability in the presence of time-dependent equilibrium, J. Geophys. Res., 102 (A8). Batista I. S., Abdu M. A. and A. J. Bittencourt, 1986: Equatorial F region vertical plasma drift: seasonal and longitudinal asymmetries in the American sector, J. Geophys. Res., 91 (A11). Burke W. J., G. S. Sagalyn Rastogi, M. Ahmed, F. G. Rich, D. E. Donatelli, P. J. L. Wildman, 1979: Postsunset refilling of the low-latitude topside ionosphere, J. Geophys. Res., 84 (A8). Chandra H., Rastogi R.G., 1972: Spread F at magnetic equatorial station Thumba, Annales Geophysicae, 28 (1), 37-44. Dao, E., M. C. Kelley, P. Roddy, J. Retterer, J. O. Ballenthin, O. de La Beaujardiere, and Y.-J. Su, 2011: Longitudinal and seasonal dependence of nighttime equatorial plasma density irregularities during solar minimum detected on the C/NOFS satellite, Geophys. Res. Lett., 38, L10104, doi:10.1029/2011GL047046. Gentile L.C., W.J. Burke, and F.J. Rich, 2006: A climatology of equatorial plasma bubbles from DMSP 1988 - 2004, Radio Sci., 41 (RS5S21). Gentile, L. C., W. J. Burke, P. A. Roddy, J. M. Retterer, and R. T. Tsunoda, 2011: Climatology of plasma density depletions observed by DMSP in the dawn sector, J. Geophys. Res., 116, A03321, doi:10.1029/2010JA016176. Hoàng Thái Lan, Nguyễn Thu Trang, John MacDougall, 2011: The occurrence of equatorial spread F over Ho Chi Minh City in years 2003 and 2005, Vietnam Journal of Earth Sciences, Vol 33 (No. 2), doi: 10.15625/jse.v33i2.287. Marasigan V. S. J., 1960: Spread F in Baguio through haft of a solar cycle, Journal of Atmospheric and Terrestrial Physics, 18, 43-47. Mendillo M. and Baumgardner Jeffrey, 1982: Airglow characteristics of Equatorial Plasma Depletions, J. Geophys. Res. 87 (A9), pp.7641-7652. Lyon A. J., Skinner N. J., Wright R. W., 1961: Equatorial spread F at Ibadan - Nigeria, Journal of Atmospheric and Terrestrial Physics, 21, 100-119. Rastogi R.G., Vyas G.D., 1977: Range and frequency spread F at Huancayo, Indian Academy of Sciences. Proceeding, 86A (4), 417 - 421. Sales G. S., B. W. Reinisch, J. L. Scaili, C. Dozois, 1996: Spread F and structure of ionization depletions in  the southern anomaly region, J. Geophys. Res. 101 (A12), 26819 - 26827. Thampi S.V., R. Tsunoda, L. Jose and T.K. Pant, 2012: Ionogram signatures of large-scale wave structure and their relation to equatorial spread F, J. Geophys. Res. 117 (A08314). Trần Thị Lan and Đào Thế Cường, 2013: Some characteristic of equatorial spread F at Phu Thuy over a solar cycle, Vietnam Journal of Earth Sciences, Vol 35 (No. 3). Tsunoda R.T., S.V. Thampi, T.T. Nguyen and M. Yamamoto, 2013: On validating the relationship of ionogram signatures to large-scale wave structure, J. Atmos. Solar-Terr. Phys. 103 (30), pp. 30-35. Tsunoda R. T., 2015: Upwelling: a unit of disturbance in equatorial Spread F, Progress in Earth and Planetary Science (2015) 2:9, doi 10.1186/s40645-015-0038-5. Tsunoda R. T., 1981: Time evolution and dynamics of equatorial backscatter plumes: 1. Growth phase, J. Geophys. Res. 86 (A1). Weber E. J., Buchau J., Eather R.  H., Mende S.  B., 1978: North-South Aligned Equatorial Airglow Depletions, J. Geophys. Res. 83 (A2). Weber E. J., S. Basu,T. W. Bullett, C. Valladares, G. Bishop, K. Groves, H.  Kuenzler, P. Ning, P. J. Sultan, R. E. Sheehan and J.  Araya, 1996: Equatorial plasma depletion precursor signatures and onset observed at 110 south of the magnetic equator, J. Geophys. Res. 101 (A12). Whalen J. A., 1996: Mapping a bubble at dip equator and anomaly with oblique ionospheric soundings of range spread F, J. Geophys. Res. 101 (A3). Whalen J. A., 1997: Equatorial bubbles observed at the north and south anomaly crests: Dependence on season, local time and dip latitude, Radio Science, 32 (No. 4). World Data Center A for Solar - Terrestrial Physics, 1978: U.R.S.I Handbook of ionogram interpretation and reduction. Zalesak S. T., Ossakow S.  L., Chaturvedi P. K., 1982: Nonlinear Equatorial Spread F:  The  Effect  of  Neutral  Winds and  Background  Pedersen  Conductivity, J. Geophys. Res. 87 (A1) http://seg-web.nict.go.jp/sealion/ALLFC/ionogram/index.html. www.sidc.oma.be (WDC-SILSO, Royal Observatory of Belgium, Brussels). http://wdc.kugi.kyoto-u.ac.jp/wdc/Sec3.html.